2007
DOI: 10.1080/17453670610013475
|View full text |Cite
|
Sign up to set email alerts
|

Similar effects of rofecoxib and indomethacin on the incidence of heterotopic ossification after hip arthroplasty

Abstract: Background Although indomethacin is effective in preventing heterotopic ossification (HO) after primary total hip arthroplasty, side effects are frequently observed. In the last decade a new class of drugs-the COX-2 selective nonsteroidal anti-inflammatory drugs-has been developed. To investigate the effect of these COX-2 selective NSAIDs on heterotopic ossification (HO) after primary total hip arthroplasty (THA), we conducted a randomized controlled trial using either indomethacin or rofecoxib for 7 days.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 31 publications
2
25
0
6
Order By: Relevance
“…Thus, COX-2 induction of PGE 2 production and signaling through PKA in muscle stem cells is a possible link between the inflammatory response to injury and ectopic bone formation. Although these studies have not involved the use of muscle stem cells, recent human data demonstrating that inhibition of COX-2 prevents heterotopic bone formation following hip arthroplasty are consistent with these findings (78)(79)(80).…”
Section: The Influence Of Pathologic Stress On Chondrogenesis and Endsupporting
confidence: 72%
“…Thus, COX-2 induction of PGE 2 production and signaling through PKA in muscle stem cells is a possible link between the inflammatory response to injury and ectopic bone formation. Although these studies have not involved the use of muscle stem cells, recent human data demonstrating that inhibition of COX-2 prevents heterotopic bone formation following hip arthroplasty are consistent with these findings (78)(79)(80).…”
Section: The Influence Of Pathologic Stress On Chondrogenesis and Endsupporting
confidence: 72%
“…By exposing only a small group of patients, they studied the efficacy of rofecoxib (a COX-2 in inhibitor) to prevent HO. These positive results were confirmed later in a randomised controlled trial using a large patient cohort [14]. For calculation of the number of subjects needed in this two-stage study design, the data of two historical patient groups with total hip arthroplasty from our department were used [15].…”
Section: Two-stage Study Designmentioning
confidence: 83%
“…In a previous study that was performed by our research group, we found Rofecoxib, a selective COX-2 inhibitor, equally effective as indomethacin to prevent HO after THA [13,14]. However, serious concerns were raised over the safety of this selective COX-2 inhibitor for the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed a 59% reduction (95% CI: 54%, 64%) in the risk of heterotopic ossification after hip arthroplasty in NSAID-treated patients. Recent clinical trials have reported that COX-2-selective NSAIDs are also effective in preventing heterotopic ossification after hip joint replacement [51][52][53][54].…”
Section: Heterotopic Ossificationmentioning
confidence: 99%